Penerapan Sistem Informasi Manajemen Rumah Sakit Secara Umum - Andika Fajar Nugroho; Dety Mulyanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Hospital Management Information System is a computer system that processes and integrates all health service business process flows in the form of coordination networks, reporting and administrative procedures to obtain information quickly, precisely and accurately. The hospital computer-based Management Information System is a very important supporting tool, and is a means to support hospital operational management. The application of SIMRS should be able to improve the quality of service in hospitals. The research method used is Literature Review to conclude how SIMRS is generally implemented.